Mechanisms of the Regulation of the Intestinal Na+/H+ Exchanger NHE3. (25th November 2009) - He, Peijian; Yun, C. Chris
Abstract : A major of Na + absorptive process in the proximal part of intestine and kidney is electroneutral exchange of Na + and H + by Na + / H + exchanger type 3 (NHE3). During the past decade, significant advance has been achieved in the mechanisms of NHE3 regulation. A bulk of the current knowledge on Na + / H + exchanger regulation is based on heterologous expression of mammalian Na + / H + exchangers in Na + / H + exchanger deficient fibroblasts, renal epithelial, and intestinal epithelial cells. Based on the reductionist's approach, an understanding of NHE3 regulation has been greatly advanced. More recently, confirmations of in vitro studies have been made using animals deficient in one or more proteins but in some cases unexpected findings have emerged. The purpose of this paper is to provide a brief overview of recent progress in the regulation and functions of NHE3 present in the luminal membrane of the intestinal tract.